Keusahawanan di Kalangan Mahasiswa: Kajian Kecenderungan Pelajar Muslim di Universiti Malaya - Sarif, S.; Amran, A. (2006)
slam encourages entrepreneurial development and business related activities among its followers. History shows that business plays a very important role in uplifting Muslim and Islamic culture especially during those glorious ages. The development of entrepreneur need to be inculcated since the early age of individual. The intention of being a self employed is a very first step in every individual's entrepreneurial development process. Based on the responses from the sample derived among Muslim students in University Malaya, the study discovers that they are inclined towards organizational employment compared to being self-employed.